(untitled) (Western European Journal of Linguistics and Education, 2024)
This article provides information about the merits, characteristics, terms used in the work " Muwaṭṭa’" by Imām Muḥammad Shaybānī, one of the mujtahid scholars of the Ḥanafī school, and the comments written on the work